2013
DOI: 10.1063/1.4832935
|View full text |Cite
|
Sign up to set email alerts
|

Studies on low energy beam transport for high intensity high charged ions at IMP

Abstract: Superconducting Electron Cyclotron Resonance ion source with Advanced design in Lanzhou (SECRAL) is an advanced fully superconducting ECR ion source at IMP designed to be operational at the microwave frequency of 18-24 GHz. The existing SECRAL beam transmission line is composed of a solenoid lens and a 110° analyzing magnet. Simulations of particle tracking with 3D space charge effect and realistic 3D magnetic fields through the line were performed using particle-in-cell code. The results of the beam dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The LEBT is a rather complicated optical system consisting of solenoids, bending magnets, electrostatic quadrupoles, and dipoles. Detailed beam dynamics studies in the LEBT were reported 2020 JINST 15 P12034 elsewhere [9,10]. The performance of the FRIB Front End (FE) per project specifications was successfully demonstrated shortly after the first beam commissioning started as reported in ref.…”
Section: Lebtmentioning
confidence: 96%
“…The LEBT is a rather complicated optical system consisting of solenoids, bending magnets, electrostatic quadrupoles, and dipoles. Detailed beam dynamics studies in the LEBT were reported 2020 JINST 15 P12034 elsewhere [9,10]. The performance of the FRIB Front End (FE) per project specifications was successfully demonstrated shortly after the first beam commissioning started as reported in ref.…”
Section: Lebtmentioning
confidence: 96%